Donor-supported approaches to improving extractives governance: Lessons from Nigeria and Ghana - Joanna Buckley; Neil McCulloch; Nick Travis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Donor interest in the extractives sector is based upon the premise that it represents an opportunity to improve a country's development prospects. However, in many cases the presence of extractive resources is associated with poor economic performance. As a result, some donors are trying a radically different approach. This paper explores two such programmes funded by the UK Department for International Development: the Facility for Oil Sector Transparency and Reform in Nigeria, and the Ghana Oil and Gas for Inclusive Growth programme in Ghana. The paper outlines five lessons learned from these examples. First, continual analysis is essential to understand the underlying incentives of key actors. Second, interventions need to be locally led in order to provide legitimacy for reform. Third, interventions need to be flexible and adaptive. Fourth, acceptance of an element of risk is necessary. Fifth, donors need to develop a new way of measuring impact.
Keywords: Q32; O13; O19; O55; 330; Oil and gas; natural resources; governance; politics; aid